ENNEAPTERYGWS NASIMAE A NEW SPECIES OF TRIPTERYGIID FISH FROM KARACHI COAST, NORTHERN ARABIAN SEA - Hoda, S M Shamsul (Indian Journal of Fisheries, 2011)
Enneapterygius nasimae sp. nov., collected from the Karachi coast (Buleii),northern Arabian sea, is characterised by having a crescentic or triangular blackpreanal spot, 6-9 dark oblique bars on anal fin, 5 dark blotches along the sides ofbody, the largest at the caudal base, first dorsal equal to or higher than seconddorsal, with fin formulae: Dl JII; D2 XII-XIII (usually XII); D3 9-10 (rarely 11);A I, 18-20; P 13-15 (usually 14: lower 7, upper 1-3 unbranched, and middle 5branched); C 13 (lower 2, upper 2 unbranched and middle 9 branched); LI 37-40(14-16 pored + 23-24 notched); Ltr 2-1-6.